(untitled) (Vietnam Journal of Community Medicine, 2025)
ABSTRACT Objective: To describe the patient admission and treatment outcomes during the first six months of operation at Level 2 Field Hospital No. 6. Methods: A cross-sectional descriptive study was conducted on all patients who visited, received emergency care, or were treated at Level 2 Field Hospital No. 6 from September 28, 2024, to March 5, 2025. Data were collected from the hospital’s medical record system. Results: Over six months, Level 2 Field Hospital No. 6 admitted 985 patients, with males accounting for 80.71%. The 19-40 age group made up 53.6%, and African patients constituted the largest proportion (66%). Internal medicine consultations accounted for 55.71%, trauma cases 9.44%, and infectious diseases 9.55%, including 34 cases of malaria. The recovery rate was 85.18%, with hospital admissions at 4.26% and referrals at 1.22%. Conclusion: Level 2 Field Hospital No. 6 effectively admitted and treated patients during the first six months, achieving a high recovery rate.